If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5k + -2k = 9 Combine like terms: 5k + -2k = 3k 3k = 9 Solving 3k = 9 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Divide each side by '3'. k = 3 Simplifying k = 3
| 2+2x=3+x | | 7/8(9) | | 0.2(0.09-4x)=-0.7x | | 5(x+3)=8x | | x^2+1(x^2-3)= | | z^2-9z+20/x^2+z-30 | | r(x)=A-3X | | 11x^2-17x-20=0 | | 6x+3=4x+12 | | x/x+2=6+3/x+2 | | 3(x+5)=3(5+x) | | (x-2)(x-2)=24 | | x+2(-1/3)=0 | | t+9(20)=140 | | x^2-3y=9 | | (-2^-2)/(4^-1) | | x+8=3+x+7 | | (1,3)(-2,-3)(5,11)= | | x^2-4y^2=60 | | (5x+6)(x^2+3x-4)=0 | | -6=7/3n | | 36x-60=24 | | 7/8(-9) | | 12(x-20)=48 | | (11/7)/(7/2) | | y-(-6)=(7/8)(x-9) | | 25y^3+2=y+50y^2 | | 24/1080 | | 25y^3+2=y-50y^2 | | -13=m/5 | | 8x-4x^2=0 | | x^6-3x^4+x^2-3=0 |